Efficacy of golimumab in the treatment of patients with ankylosing spondylitis (according to the data of a long-term follow-up) - A. V. Smirnov; T. V. Dubinina; Sh. F. Erdes (Современная ревматология, 2015)
The paper summarizes the data of a randomized placebo-controlled phase 3 GO-RAISE trial of spondylitis (AS) patients receiving two different doses (50 and 100 mg) of golimumab (GLM), which evaluates its efficiency and safety and X-ray progression of changes in the axial skeleton. In AS patients, GLM therapy leads to a rapid long-lasting clinical and radiological response. The tolerability of long-term therapy with GLM generally complies with the safety profile of the entire class of tumor necrosis factor-р (TNF-р) inhibitors.The data of the GO-RAISE trial has substantiated once again the established fact that the high baseline level of C-reactive protein (CRP) and the presence of syndesmophytes are predictors for a rapider X-ray progression. At the same time, the results of the trial may question the recent assumptions that TNF-р suppression can exert a stimulating effect on the formation of new bone tissue with time. Further studies are to determine whether there is an association between the presence of syndesmophytes and elevated CRP levels and whether they have a combined effect on X-ray progression, and if so, whether the development of structural changes may be prevented with TNF-р inhibitors to be used at the earlier stages of the disease.